A Shortened Version of the Reasons for Living—Older Adults Scale for Clinical and Research Utility. (26th February 2018) - Lutz, Julie; Edelstein, Barry; Katz, Emma; Gallegos, Jarred V
Abstract: Background and Objectives: Older adults have elevated suicide rates, and identification of protective factors, such as reasons for living, is important in preventing suicide. The Reasons for Living—Older Adults scale (RFL-OA) is a 69-item measure of these protective factors in late life, which yields good psychometric properties. However, its length limits its utility in some clinical and research contexts where a shorter measure is ideal. The objective of this study was to create a shortened version of the RFL-OA. Research Design and Methods: First, data collected previously during validation of the original RFL-OA ( n = 199, age 65 and older, 65% female) were used to select 30 items, spanning all content areas, that were highly endorsed. Second, new data were collected ( n = 219, age 60 and older, 52% female) with the 30-item RFL-OA and measures of depression, hopelessness, suicidal ideation, religiosity, health, and social desirability to examine the measure's internal consistency and convergent and discriminant validity. Results: Scores on the 30-item RFL-OA exhibited strong internal consistency. The short RFL-OA demonstrated good convergent validity via significant, moderate correlations with suicidal ideation, hopelessness, depression, and religiosity. It demonstrated adequate discriminant validity via only small correlations with disability, subjective health, and social desirability. Discussion and Implications: The shorter RFL-OA has good psychometric properties among community-dwelling older adults. It may have greater utility, compared to the original 69-item measure, for clinicians and researchers with limited time but who want to assess protective factors against suicidal behavior in late life.